The declaration of the victim in criminal proceedings for gender violence and ambivalences of the criminal justice system - Eliana Aleman (Oñati Socio-Legal Series)
This article examines the behaviour of the variable “victim’s declaration” in the police and the court in criminal proceedings for gender violence, problematizing the results from a sociological and gender perspective. From a quantitative methodology, the analysis of the procedures initiated during 2017 in the Pamplona judicial district allows us to identify frequencies and statistically significant relationships of this variable with others. The importance of the victim is verified so that the process reaches trial phase. It constitutes an empirical contribution to the theoretical and dogmatic works that analyse the criminal justice system from a gender perspective. It contributes to the legal and social debate on the need for the victim's declaration to obtain effective judicial protection, identifying the rationale behind this demand. The ambivalence of the system that requires a moral consensus around the victim to obtain legitimacy is appreciated.